Software Package for Special Teaching and Testing of Children with Hearing and Speech Impairments - Stolyarova E.I.; Belova N.Yu.; Solnushkin S.D.; Chikhman V.N. (Психолого-педагогические исследования)
The paper presents a description of the software package (code name “Speech-Assistant”), intended for use in special education and testing of children with hearing and speech impairments, causing difficulties in mastering reading and writing skills. An attempt has been made to create a software package capable of sufficiently providing both the solution of various research problems and the expansion of opportunities for increasing the effectiveness of teaching and developmental lessons in practical application in the educational process. When designing it, the wishes of practicing special teachers (defectologists) and the results of studies of auditory perception and speech skills in children with hearing and speech disorders, carried out in the laboratory of speech psychophysiology of the Pavlov Institute of Physiology RAS. The complex includes three thematic blocks: “Learn to listen”, “Learn to read”, “Exercises”. The programs of the complex provide the convenience of the teacher's independent preparation of didactic material for the planned lessons, the implementation of a wide range of educational tasks, and their preservation for repeated use. In the process of conducting lessons, objective indicators of assignments are recorded, a digital archive of the training or testing results is automatically generated in the database in the form of personalized excel and wav-files. The article presents materials that illustrate the capabilities of the complex when performing tasks from the above thematic blocks. The approbation of the complex working was carried out within the framework of training sessions in 5-9th classes of a specialized school.